A Fast Chi-squared Technique For Period Search of Irregularly Sampled Data - Palmer, David M (arXiv.org, 2009)
A new, computationally- and statistically-efficient algorithm, the Fast \(χ^2\) algorithm, can find a periodic signal with harmonic content in irregularly-sampled data with non-uniform errors. The algorithm calculates the minimized \(χ^2\) as a function of frequency at the desired number of harmonics, using Fast Fourier Transforms to provide \(O (N \log N)\) performance. The code for a reference implementation is provided.